Peran Kementerian Agama dalam Pengentasan Kemiskinan di Jawa Tengah - Miftakhudin Miftakhudin (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2024)
This study describes the role of the Ministry of Religious Affairs (MoRA) in alleviating poverty in Central Java through two main approaches: the empowerment of micro, small, and medium enterprises (MSMEs) and the implementation of the waqf program. The Ministry of Religious Affairs through the Office of Religious Affairs for the Economic Empowerment of the Ummah (KUA PEU) program, which is a program of assistance and strengthening access to family/community-based community economic empowerment consisting of providing assistance for community economic empowerment, training, business workshops and business assistance to MSME entrepreneurs, has contributed significantly to improving economic welfare. Then through the Productive Waqf Incubation Program, a program that is a vehicle for transforming the formation of nazir human resources into human resources who have a creative business spirit. Innovative and visionary. Nazirs receiving assistance will get access to capital, training and mentoring. Despite challenges, such as low awareness of waqf, education strategies and collaboration with stakeholders were identified as key factors for the sustainability and expansion of the program. Recommendations include raising awareness, strengthening collaboration, and further developing the MSME empowerment program for sustainable impact. this policy paper provides a comprehensive understanding of MoRA's role in poverty alleviation, integrating economic empowerment with religious principles.